Taxonomy and phylogeny of Pseudovorticella ciliates (Ciliophora, Peritrichia): Two new and one rare species from the coastal waters of China - Zhang, Yong; Yu, Ying; Qu, Zhishuai; Jiang, Mengmeng; Shen, Zhuo; Li, Jiqiu; Lin, Xiaofeng (Frontiers in Marine Science, 2022)
Peritrich ciliates are a species-rich group of sessile unicellular eukaryotes, which can be found in various aquatic habitats from all over the world. It is well accepted that there are still many ciliates to be uncovered. During a survey on ciliate biodiversity in the coastal waters of China, three solitary peritrich species were identified as members of the genus Pseudovorticella Foissner & Schiffmann, 1975, including two new species and a rare one. Pseudovorticella zhejiangensis sp. n. differs from its congeners mainly by having a conical-shaped zooid, conspicuous pellicular blisters, one ventral and one dorsal contractile vacuoles, and an infundibular polykinety 3 with three rows of nearly equal length but different beginning positions. Pseudovorticella dalianensis sp. n. can be defined mainly by an obovoid-shaped zooid, one ventral contractile vacuole, and a three-rowed infundibular polykinety 3 with the middle row being the longest. The rare species, Pseudovorticella verrucosa (Dons, 1915) Sun et al., 2009, was redescribed. The small subunit (SSU) rDNA sequences of these three species were sequenced for the first time, the phylogeny of Pseudovorticella species was analyzed, and the results verified the non-monophyly of this genus. This study demonstrates that the morphologic and gene barcoding data are the optimum combination to disclose the biodiversity of ciliates.